1997
DOI: 10.2307/2446006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fasciation mutation in apical Meristems of Soybean, Glycine Max (Leguminosae)

Abstract: The phenotype of the apical meristem was used to examine the effect of fasciation mutation at the f locus in different genetic backgrounds in soybean Glycine max (L.) Merr. Comparisons of meristem development in fasciation mutant and wild type were conducted with scanning electron microscope (SEM) on isogenic lines BARC-11-11-ff and BARC-11-11-FF at postgermination and early vegetative stages. Studies of apical meristems of three independently originated fasciation mutants, PI 83945-4, PI 243541, and T173, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…2-A) as observed in fasciated soy bean (Tang et al 1997). Epidermal cells, stomates and rhizoids in the fasciated rhizome were similarly orientated towards the base (Fig.…”
supporting
confidence: 54%
“…2-A) as observed in fasciated soy bean (Tang et al 1997). Epidermal cells, stomates and rhizoids in the fasciated rhizome were similarly orientated towards the base (Fig.…”
supporting
confidence: 54%
“…Seventy percent of the pods are located at the top of the main stem in fasciated soybean (Wongyai et al, 1984). The soybean fasciation trait is controlled by a single recessive gene (White, 1945;Albertsen et al, 1983;Wongyai et al, 1984;Leffel, et al, 1993;Tang and Skorupska, 1997). In both normal and fasciated subtypes of determinate-type soybeans, the fl owering duration is shorter than that in the indeterminate type (Yoshida et al, 1983;Foley et al, 1986;Saitoh et al, 1998).…”
mentioning
confidence: 99%
“…Moreover mapping analyses of the fasciation locus performed here as well as in a previous study (Karakaya et al 2002) showed that the fasciation genes originating from Shakujodaizu, Taikadaizu and Shakujomame were probably identical. Morphological and agrobiological characteristics have been well evaluated in several studies (Albertsen et al 1983, Tang and Skorupska 1997, Tang and Knap 1998, Wongyai et al 1984. The morphological changes on the shoot apical meristem (SAM) did not result from fusion of two or more meristems but were caused by enlargement, followed by growth along one axis or sub-angular growth of a single apical meristem (Tang and Skorupska 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological and agrobiological characteristics have been well evaluated in several studies (Albertsen et al 1983, Tang and Skorupska 1997, Tang and Knap 1998, Wongyai et al 1984. The morphological changes on the shoot apical meristem (SAM) did not result from fusion of two or more meristems but were caused by enlargement, followed by growth along one axis or sub-angular growth of a single apical meristem (Tang and Skorupska 1997). Soybean varieties with fasciation showed a wide variation in the degree of stem fasciation with a noticeably different pattern of pod setting pattern (Wongyai et al 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation